STAT5b is a key effector of NRG-1/ERBB4-mediated myocardial growth - Vaparanta Katri; Jokilammi Anne; Paatero Ilkka; Merilahti Johannes A; Heliste Juho; Hemanthakumar Karthik Amudhala; Kivelä Riikka; Alitalo Kari; Taimen Pekka; Elenius Klaus (EMBO Press, 2025)
The growth factor Neuregulin-1 (NRG-1) regulates myocardial growth and is currently under clinical investigation as a treatment for heart failure. Here, we demonstrate in several in vitro and in vivo models that STAT5b mediates NRG-1/EBBB4-stimulated cardiomyocyte growth. Genetic and chemical disruption of the NRG-1/ERBB4 pathway reduces STAT5b activation and transcription of STAT5b target genes Igf1, Myc, and Cdkn1a in murine cardiomyocytes. Loss of Stat5b also ablates NRG-1-induced cardiomyocyte hypertrophy. Dynamin-2 is shown to control the cell surface localization of ERBB4 and chemical inhibition of Dynamin-2 downregulates STAT5b activation and cardiomyocyte hypertrophy. In zebrafish embryos, Stat5 is activated during NRG-1-induced hyperplastic myocardial growth, and chemical inhibition of the Nrg-1/Erbb4 pathway or Dynamin-2 leads to loss of myocardial growth and Stat5 activation. Moreover, CRISPR/Cas9-mediated knockdown of stat5b results in reduced myocardial growth and cardiac function. Finally, the NRG-1/ERBB4/STAT5b signaling pathway is differentially regulated at mRNA and protein levels in the myocardium of patients with pathological cardiac hypertrophy as compared to control human subjects, consistent with a role of the NRG-1/ERBB4/STAT5b pathway in myocardial growth.